EU KIT204 - Ioannides, Marinos (My University, 2026)
This project considers the application of surface modelling and rapid prototyping technologies to the prototyping and/or the reproduction of exact models in architecture, archaeology and geodesy. Furthermore, it deals with applications of 3D modelling, visualisation and rapid prototyping in medical diagnosis, surgical planning, radiation therapy planning, and the precision milling of prostheses. The research institute INRIA at Sofia-Antipolis in France, developed a software model for the reconstruction of medical objects. This model was integrated into the Surface Modelling System of the HTI and was further developed to a more advanced stage. The ISW sent a 3-D laser scanner to the HTI in order to digitise the temple stones of Venus to facilitate the temple's reconstruction. The HTI was able to reconstruct the Temple of Venus. With help of the digitised data a 1:140 model was made using stereolithography. Research Scientists from the ISW and HTI visited the Louvre in Paris. This was necessary in order to digitize the world's largest vase, which happens to originate from Cyprus. This vase is used as a demonstration object for the developed software packages due to its nonuniform surface. The vase will be reconstructed using the Surface Modelling System to provide a full size duplication.
Keywords: Sciences